KINERJA DAN KEBERLANGSUNGAN PERUSAHAAN DALAM PENERAPAN SISTEM ERP: TINJAUAN SISTEMATIK LITERATUR - Ghaliyah Nimassita Triseptya; Andi Zulfakar Yudha (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
This study aims to analyze the development of research on Enterprise Resource Planning (ERP) and to identify the impact of ERP implementation on corporate performance and sustainability. The study employs a Systematic Literature Review (SLR) method, with data sourced from the Scopus database. The selection process was conducted through several screening stages based on the publication period (2015–2025), journal quality (Q1–Q3), topic relevance, and article accessibility. Out of 139 identified articles, 21 met the inclusion criteria and were selected for analysis. The findings indicate that ERP research is predominantly focused on supply chain integration and digital transformation, ERP implementation success factors, and the development of Sustainable ERP (S-ERP). The factors most frequently associated with ERP success include supply chain integration, sustainability practices, information quality, change management, and organizational factors. ERP implementation has been shown to positively affect corporate performance by improving operational efficiency, information quality, supply chain integration, and sustainability performance. Furthermore, the literature suggests that the integration of ERP with sustainability strategies, the strengthening of change management practices, and the adoption of technologies such as the Internet of Things (IoT), Blockchain, and Building Information Modeling (BIM) represent important directions for future research. The most commonly applied theories in ERP studies are the Resource-Based View (RBV), Technology–Organization–Environment (TOE) Framework, Institutional Theory, Diffusion of Innovation (DOI) Theory, and Change Management Theory. These findings demonstrate that ERP serves not only as a tool for business process integration but also as a strategic resource that supports long-term improvements in corporate performance and sustainability